Cáster River (Ovar, Portugal): Evaluate to Recover - Polónia, R.; Santos, J. R. (Open Schools Journal for Open Science, 2020)
The Cáster is the largest river in the Municipality of Ovar, flowing into the northern arm of the Ria de Aveiro (a coastal Haff-Delta). It constitutes a threatened ecosystem that has suffered a marked degradation of water quality, a decrease in biodiversity, an increase in human pressure on the margins, and several problems in the regularity of the flow itself. In this project we intend to evaluate, through physical-chemical and biological methods, the quality of the water, monitor fluctuations in flow rates, identify polluting sources, and, based on the data collected, develop intervention proposals, in support of local entities. In partnership with the Science Club, some devices (Arduino and Raspeberry enabled) are being developed for continuous remote monitoring of different areas of the river.